Money Attitude, Self-esteem, and Compulsive Buying in a Population of Medical Students - Lejoyeux, Michel; Richoux-Benhaim, Charlotte; Löhnardt, Hannah; Lequen, Valérie (Frontiers in Psychiatry, 2011)
This study tried to determine the prevalence of compulsive buying (CB) and to identify among compulsive buyers a specific relation to money, a different buying style and a lowered level of self-esteem. We included 203 medical students and diagnosed CB with the Mc Elroy criteria and a specific questionnaire. The money attitude was characterized by the Yamauchi and Templer’s scale and self-esteem with the Rosenberg scale. 11% of the medical students presented compulsive buying (CB +). Sex ratio and mean ages were comparable in the CB+ and control groups. CB+ students drank less alcohol and smoked an equivalent number of cigarettes. Compulsive buyers had higher scores of distress (tendency to be hesitant, suspicious and doubtful attitude toward situations involving money) and bargain missing (fear of missing a good opportunity to buy an item). They bought more often gifts for themselves, items they use less than expected and choose goods increasing their self-esteem. Their score of self-esteem was not different from the one from controls.